Penerapan Norma-Norma Sosiokultural Dalam Berbahasa Pada Penutur Bahasa Simalungun Perantauan Dikota Jambi - Arnold Harun Purba; Andiopenta Purba; Akhyarudin Akhyarudin (Jurnal Ilmiah Dikdaya, 2026)
This qualitative research aims to identify and examine the sociocultural norms in interaction and interpretation, as well as to analyze the transformation of communication culture among Simalungun language speakers in Jambi City. Data were collected using participatory observation and in-depth interviews with the Simalungun community residing in the research location. The data analysis technique employed was speech situation data analysis, focusing on the context supporting the utterances in a conversation. The data analysis process involved three interactive stages: data reduction, data presentation, and conclusion drawing, performed throughout the research period. The findings reveal that the sociocultural norms among Simalungun speakers in Jambi City are divided into three main categories. First, Sociocultural Norms of Interaction, which include five sub-norms: (1) granting turn-taking opportunities to the interlocutor, (2) demonstrating a sympathetic attitude towards the interlocutor's speech, (3) avoiding interruption of the interlocutor, (4) apologizing for not meeting the interlocutor's expectations, and (5) expressing gratitude for attention and service. Second, Sociocultural Norms of Interpretation, encompassing three aspects: (1) attitude and body gestures (posture, hands, facial expressions, and eye contact), (2) inquiring about personal status (occupation, marital status, age, and social status), and (3) maintaining appropriate physical distance between the speaker and the interlocutor. Third, the study identified Sociocultural Norms in the Transformation of Communication Culture. These findings contribute to understanding the linguistic dynamics of migrant ethnic groups within a different cultural environment.